I married a dead man - Woolrich, Cornell, 1903-1968 (Centipede Press, 2012)
"Happenstance. Perhaps a wonderful bonanza, possibly an unmerciful future. Without thinking to possess it, suddenly the brass ring is there, poised for the taking. Everyone believes it is yours, and once you dare to possess it, those who don't even know you, accept you as one of their own, a member of the clan. So, why not embrace the dream-like life being offered to you on a silver platter? What is the down side to becoming a member of the privileged class? What is the harm? Herein lies the trap ..."--Dust jacket, front flap.